Field, probabilistic and 2D numerical modeling dataset on gravel mobility in the Ain River (2013-2017) - Fanny Arnaud; André Paquier; Daniel Vázquez-Tarrío; Benoit Camenen; Jérôme Le Coz; Kristell Michel; Grégoire Naudet; Hervé Pella; Hervé Piégay (PANGAEA, 2023)
This dataset presents field sediment tracking surveys, two-dimensional hydrodynamic modeling outputs and comparison with a probabilistic approach to assess gravel mobility in the Ain River in Eastern France, as part of a gravel augmentation program to mitigate sediment deficit below the Allement Dam. The 4 km-long study site is located on the sediment-starved reach of the Lower Ain River, between the Terre Soldat bank and the downstream part of the Priay village. 1063 tracer stones were equipped with radio-frequency Passive Integrated Transponders (PIT tags) and released in the Ain River channel at Terre Soldat in 2013. Tracer stones were detected and geolocated after flood events in 2014, 2015 and 2017. A two-dimensional hydrodynamic model was constructed on the Lower Ain River using the Rubar20 software. The model was ran to obtain the steady flow patterns at the three flow discharges of 350, 500, and 760 m3/s, which correspond to the critical discharge for incipient bedload transport, an intermediate flow discharge, and the peak flow discharge for a duration of two hours that occurred over the studied period 2013–2017. The modeled trajectory of particles was calculated from hydrodynamic modeling results. Finally, a probabilistic approach based on published tracer studies was used to model tracer particle dispersion in the Ain River. Our dataset allows assessing the strengths, weaknesses, and complementary aspects of three approaches to the understanding of river gravel mobility. This bundled publication contains six datasets.